Subgrain boundary engineering enables synergistic improvement of strength and corrosion resistance in an Al-Cu-Li alloy - Siyan Liang; Li Liu; Xiaoya Wang; Jiantang Jiang; Liang Zhen (Materials & Design, 2025)
Al-Cu-Li alloys with a high fraction of subgrain boundaries are generally prone to inter-subgranular corrosion (IsGC), restricting their application in critical structural components. This study proposes a subgrain boundary engineering strategy combining cold rolling and artificial ageing to simultaneously enhance the strength and corrosion resistance of an Al-Cu-Li alloy. The engineered alloy exhibited superior IsGC resistance, with a 63 % reduction in maximum corrosion depth and corrosion current density compared to the T6 sample, alongside 12 % higher yield strength and 13 % increased elongation. Cold rolling introduces numerous dislocations, promoting fine intragranular T1 precipitation while suppressing T1, Mg-rich θ' and S' phases precipitation on subgrain boundaries, reducing micro-galvanic effects. Synchrotron XRD and critical resolved shear stress model were employed to elucidate the strengthening mechanisms. The strain-induced dislocation multiplication increases the strain hardening ability, and the refined precipitate size mitigates the stress concentration around large non-shearable precipitates. The present engineering strategy provides a promising approach for developing high-performance Al alloys.